Trends in incidence rates of acute myocardial infarction and stroke among immigrant groups in Norway, 1999–2019: the NCDNOR project - Rabanal, Kjersti Stormark; Selmer, Randi Marie; Igland, Jannicke; Ariansen, Inger; Meyer, Haakon Eduard (Open heart, 2025)
AimsWe aimed to study time trends of acute myocardial infarction (AMI) and stroke incidence rates among immigrant groups living in Norway, with a special focus on immigrants from South Asia and former Yugoslavia.MethodsAll incident AMI and stroke events were identified in Norwegian residents aged 35–79 years during 1996–2019 using hospital and cause of death registry data. A 3-year wash-out period was used to identify incident events. Thus, cases were counted from 1999 onwards. We calculated annual age-standardised incidence rates using direct standardisation. Poisson regression was used to calculate the average annual change in incidence rates of AMI and stroke and to study differences between immigrant groups and the Norwegian-born population.ResultsAge-standardised incidence rates of AMI were higher in immigrants from South Asia and former Yugoslavia than in the Norwegian-born population. For Norwegian-born men and women, and former Yugoslavian women, the annual age-standardised AMI incidence rates declined over the study period by 2.4%, 2.0% and 2.3%, respectively. South Asian men and women and former Yugoslavian men did not experience such a decline, although there was an apparent decline in the last 3 years of the period for South Asian men. For former Yugoslavian men, this resulted in increasing differences compared with Norwegian-born men. For stroke, all these groups had declining trends in incidence rates, and former Yugoslavian women had the strongest decline of 4.3% annually.ConclusionDuring 1999–2019, immigrants from South Asia and former Yugoslavia did not experience the same beneficial decline in AMI incidence as the Norwegian-born population. However, both immigrant groups experienced similar or larger declines in the incidence of stroke as Norwegian-born men and women.